Aplicação da ferramenta “barômetro da sustentabilidade” em estudos de bacias hidrográficas urbanas - Fonseca, Luany Weiler da (2013)
The terms sustainability and sustainable development have always been used interchangeably in the literature whose essence is given by the interaction between: environmental conservation , social equity and economic development. This paper aims to apply the general tool Sustainability Barometer studies in urban watersheds, whose object of study is the watershed stream Caju. This watershed is located in the Cuiabá river basin, sub-basin of the river Coxipó, in the urban area of Cuiabá-MT, specifically in the neighborhoods CPA II and CPA III, between the geographical coordinates 15°33'32 " 15°34'35" south latitude and 56 ° 02'51 " 56 ° 02'21 " west longitude from Greenwich . The tool requires the construction of a framework of sustainability performance indicators which were selected by means of the production of primary data from campaigns and field survey and research on secondary data from various sources. The field campaigns were carried out from july/2011 to july/2012, aiming to collect water samples for analysis of variables: hydrogen potential, dissolved oxygen, turbidity, biochemical oxygen demand, phosphorus total, orthophosphate, total kjeldahl nitrogen, water temperature and chlorophyll a. The quality of stream water Caju is very committed. The degree of sustainability of the system (watershed) needs to be improved, especially in relation to environmental degradation, where several indicators influenced negatively their well being, such as those related to water quality: conformity to the biochemical oxygen demand, the trophic level of water body and water pollution by solid waste.